Fungal infections in patients with chronic liver disease: mortality and associated risk factors - Rasool, Shahid; Babar, Ahmad N.; Shafquat, Umair; Azhar, Salman; Khan, Rizwan R. (International Journal of Research in Medical Sciences, 2019)
Background: Patients with chronic liver disease are immunocompromised and prone to different opportunistic infections. Fungal infections in patients admitted with liver cirrhosis are not rare and they may increase mortality and morbidity of these patients. Aims of the study is to determine the mortality and its risk factors associated with fungal infections in patients with chronic liver disease. Methods: In this retrospective study, patients admitted with chronic liver disease during the last four years on this hospital were studied for diagnosed fungal infections. A matched control group of cirrhosis patients with a ratio of 1:2 admitted without fungal infections was also studied and mortality was compared between the two groups. Results: Seventy admitted patients of liver cirrhosis with microbial and histopathological evidence of fungal infection were found while 140 patients of the control group had no evidence of fungal infection. Hepatitis C virus infection was the major cause of cirrhosis (65%) and most of the patients were in child class C(63%). Urinary tract infection, esophageal candidiasis, and mucormycosis were major fungal infections. Mortality was much higher in the fungal infections group (34.3%) as compared to the non-infectious group (16%). On multivariate analysis, high WBCs count, hypo-albuminemia and high creatinine levels were the worst factors affecting mortality. Conclusions: Fungal infections are a significant cause of morbidity and mortality in patients with decompensated cirrhosis. Advanced cirrhosis, renal insufficiency, and leucocytosis are independent predictors of fatal outcome in these patients.